The block programming of information resources’ distribution in a one-way wireless data transmission network - Печурин, Н. К.; Кондратова, Л. П.; Печурин, С. Н. (Problems of Informatization and Control, 2015)
The considered in the article problem of information resources’ distribution in a one-way wirelessdata transmission network is described by a mathematical model with the restrictions’ system, whichhas the block diagonal structure. The application block programming of Danzig-Wolfe fordetermining the permissible minimum cost flow with separating the independent blocks of restrictionson the first level of decomposition allows to obtain the solution which is comparable with the result ofthe classical flow algorithms executing on reducing the resource expenses